2009
DOI: 10.1080/09585190902770760
|View full text |Cite
|
Sign up to set email alerts
|

Rhetoric but whose reality? The influence of employability messages on employee mobility tactics and work group identification

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 36 publications
1
31
0
3
Order By: Relevance
“…Crouch (2006) suggests that investing in a given skill or body of knowledge is a gamble, because it is impossible to gauge beforehand whether it will be of any use. Managers who are adamant about employability tend to be able to make only vague statements about what exactly employees should learn (Hallier 2009). Hirsch and Shanley (1995) remind us that a traditional careers system offers focus, coordination and a reduction of uncertainty that helps employees invest effectively in themselves.…”
Section: Theoretical Constraintsmentioning
confidence: 98%
“…Crouch (2006) suggests that investing in a given skill or body of knowledge is a gamble, because it is impossible to gauge beforehand whether it will be of any use. Managers who are adamant about employability tend to be able to make only vague statements about what exactly employees should learn (Hallier 2009). Hirsch and Shanley (1995) remind us that a traditional careers system offers focus, coordination and a reduction of uncertainty that helps employees invest effectively in themselves.…”
Section: Theoretical Constraintsmentioning
confidence: 98%
“…Workers need to acquire other skills or attributes, usually soft skills or interpersonal skills, particularly in sectors where work requires customer interaction (Marks and Scholarios, 2007). It has been suggested that employability is the excuse given to workers ‘in the face of shrinking career opportunities and the passing of stable employment’ (Hallier, 2009: 846).…”
Section: Background and Introductionmentioning
confidence: 99%
“…It enables employees to move around in order to find a better work environment and, even if they do not change jobs, it gives them a sense of being able to cope with current circumstances; a privilege that low-employability employees may not have (Berntson & Marklund, 2007). Employability is also indicative of the new psychological contract that exists between employees and employers (Hallier, 2009). Highly employable employees feel that they are capable of dealing with current and future developments, including the changes in the psychological contract, and this is likely to enhance their well-being .…”
Section: Perceived Employability Employee Well-being and Intention Tmentioning
confidence: 99%